THE IMPLEMENTATION OF TRAINING-COACHING-INSPIRING MODEL IN MANAGERIAL TRAINING AND EVALUATION OF ENGLISH BASED INSTITUTIONS - Khairun Nisa; Neni Afrida Sari Harahap (Jurnal Intelek Insan Cendikia, 2025)
This study aimed at investigating the aspects and phases of Training-Coaching-Inspiring (TCI) Model in managerial training and evaluation of English Based Institution. It was a case study at HERO English Course Medan. The research employed a qualitative case study method which was focusing on a single informant the academic manager at HERO English Course in Medan, Indonesia. Data were collected through semi-structured interviews and document analysis. The findings revealed that HERO applies a structured three-phases training model known as "Training, Coaching, and Inspiring" (T-C-I). The training emphasizes technical teaching skills through microteaching and interactive methods; coaching provides personalized mentoring based on students’ psychological and academic profiles; and inspiring includes motivational sessions with alumni to foster learner aspirations. The findings encouraged all English institutions to implement the specific strategies, model and approaches in managerial training and evaluation for staff institution, especially in an English Course Institution.